The Influence of Work Management and Work-Life Balance on Work Productivity - Ferdiansyah, Ilham (Lentera Ilmu Nusantara, 2024)
This research aims to find out how much influence work management and work life balance have on work productivity. This research took samples from employees working at Bekasi Regency Companies which received 65 respondents. The method used is a quantitative survey research method which is carried out by distributing questionnaires which include statements regarding work management issues, work life balance and work productivity. The results of this research found that work management has a significant positive effect on work productivity and work life balance has a weak effect on work productivity.